Constituição e desenvolvimento da educação superior a distância no Brasil : as contribuições do Conselho Federal de Educação (1992-1994) e do Conselho Nacional de Educação (1995-2014) - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
This dissertation is linked to the Research Line "Education, Schools and Technologies" at the Interdisciplinary Master's Program for Education, Languages and Technologies at the Universidade Estadual de Goiás (UEG). The overall objective is to analyze the measures of regulatory acts of the Federal Council of Education (FCE) and the National Education Council (NEC) contributed to the establishment and development of higher education distance. It is a qualitative research, performed by means of literature and documentary research, with data collected in the NEC 's library, specifically at Documenta magazine and digital files made available by the institution. Regulatory acts were consulted (resolutions, opinions and statements) that are intended for higher education distance and sent in the FCE duration since 1962 until 1994, and the NEC, since 1995 until the last year of the first term of government Dilma, in 2014. The collected data were analyzed from the councils established functions in their respective creation and internal regulations laws, supported by theoretical public policy cycle, focusing on formulation stage. To present the fundamentals of distance education, studies of Moore and Kearsley (2007) were very important, as well as Lima (2013), Peters (2006) and Toschi (2013). In order to explain about the legal and expansion of distance education in Brazil in recent decades, has become relevant Alonso studies (2010), Gold (2008), Ferreira (2012), Giolo (2010) and Lima (2014a, 2014b). For input and elucidation of the concept of state, government and public policy, it highlights the studies made by Campos (2005); Dias (2013); Howlett, Ramash and Perl (2013) and Rodrigues (2011). Seeking to recognize the Council's locus on management structure of the national education and as a organic of Executive authority, in other words, not as those who have power and autonomy to legislate, but as a space to propose measures and comment about issues surrounding the agendas and disputes to draft a public policy, have been important studies made by Bordignon (2010), Cury (2006, 2011) and Gohn (2006a; 2006B). It was determined that the FCE participated more actively on discussions for use of higher education distance, through their statements, opinions and reports of committees, including barring the creation of a public open university for lack of adequate infrastructure, however, ended his acting authorizing many specialization courses in the form of private Higher Education Institutes. In relation to the NEC, we observed a decrease in activity of study groups from the normative acts analyzed, since it is restricted to resolutions and opinions, and generally treat of direction for the operation of the Higher Education Institutes.
Keywords: Atos normativos para EAD; Educação superior; Educação a distância; Conselho Federal de Educação; Conselho Nacional de Educação; Normative acts for DE; Higher education; Distance education; Federal Council Education; National Council Education; CIENCIAS HUMANAS::EDUCACAO